Conventional and Specialty Eggplant Varieties in Florida - Monica Ozores-Hampton (EDIS)
Eggplants are members of the nightshade family Solanaceae. Cultural practices employed in eggplant production are similar to tomatoes and peppers. In south Florida, where winters are mild and freezes are infrequent, eggplants are planted from August to March. This 5-page fact sheet is a guide to eggplant varieties commonly used in Florida. Written by Monica Ozores-Hampton, and published by the UF Department of Horticultural Sciences, October 2014.